2006
DOI: 10.1186/1471-244x-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Mental health consultations in a prison population: a descriptive study

Abstract: Background: The psychiatric morbidity among prison inmates is substantially higher than in the general population. We do, however, have insufficient knowledge about the extent of psychiatric treatment provided in our prisons. The aim of the present study was to give a comprehensive description of all non-pharmacological interventions provided by the psychiatric health services to a stratified sample of prison inmates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 30 publications
2
30
3
3
Order By: Relevance
“…This indicates their tendency to develop mental disorders such as post-traumatic stress disorder in the near future. This finding is also supported by the study of Johan, Bjorngard, Rustad, and Kjelshberg,[26] who found that prisoners are characterized by elevated mental and physical health related morbidity. Kane[11] reported in his study that more than 8 in 10 prisoners have chronic physical mental or substance abuse conditions.…”
Section: Discussionsupporting
confidence: 71%
“…This indicates their tendency to develop mental disorders such as post-traumatic stress disorder in the near future. This finding is also supported by the study of Johan, Bjorngard, Rustad, and Kjelshberg,[26] who found that prisoners are characterized by elevated mental and physical health related morbidity. Kane[11] reported in his study that more than 8 in 10 prisoners have chronic physical mental or substance abuse conditions.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is comparable with other studies that have reported a high rate of psychiatric disorders among inmates (Agbahowe et al, 1998;Otakpo & Asikhia, 2000;Teplin et al, 2002;Abram, Teplin, McClelland, & Dulcan, 2003;Kjelsberg, Hartvig, Bowitz, Kuisma, Norbech, Rustad, Seem, & Vik, 2006;Trestman, Ford, Zhang, & Wiesbrock, 2007). This prevalence was however higher than the previously reported rate of 34% by Agbahowe et al (1998) in a study among inmates in Benin, Nigeria but lower than the rate (78.7%) obtained by Otakpo and Asikhia (2000).…”
Section: Discussionsupporting
confidence: 94%
“…The developments in effective therapies for Personality Disorders (Bernstein, Arntz, & Vos, 2007;Farrell, Shaw, & Webber, 2009;Nadort et al, 2009;van Asselt et al, 2008) suggest that psychotherapeutic interventions reducing factors underlying antisocial behavior should be a key area of investment when dealing with personality-disordered inmates (Gilbert & Daffern, 2011;Kjelsberg et al, 2006). Similarly to what is done in the case of substance dependence/abuse, differential treatment for subjects with severe personality pathology should be provided to ensure adequate treatment and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%